Locking Plate Fixation for Canine Acetabular Fractures - Piana, Francesco; Solano, Miguel; Kalff, Stephen; Yeadon, Russell (Veterinary and Comparative Orthopaedics and Traumatology, 2020)
Objective The aim of this study was to document application of locking plates for stabilization of acetabular fractures along with complications and clinical outcomes. We hypothesized that complications and clinical outcomes would be comparable to historical reports using non-locking plate and screw constructs.Study Design Medical records of dogs presented with acetabular fractures at a single referral centre between 2010 and 2018 were reviewed. Cases surgically managed by open reduction and internal fixation, involving placement of at least one locking plate and screws, were included. Signalment, fracture classification, type of implant used, additional methods of stabilization, along with complications and neurological deficits, were collected. Long-term follow-up was based on Liverpool Osteoarthritis in Dogs questionnaire.Results Eighteen acetabula were repaired in 17 dogs. Locking implants were VetLOX (4/18), string-of-pearls (7/18) and locking compression plates (7/18). Locking plates and screws were used as the sole method of fixation in 10/18 acetabula, and as adjunctive fixation with other implants in 8/18 acetabula. Two minor complications and one catastrophic complication were reported. Sixteen of seventeen dogs returned to function with radiographic documentation of fracture healing. Complication rate was comparable to historic reports using non-locking implants. Long-term outcomes assessed by Liverpool Osteoarthritis in Dogs questionnaire were positive in most cases.Conclusion Locking plates are a viable means of stabilizing acetabular fractures in dogs and can provide positive clinical outcomes. Surprisingly, problems including inaccurate fracture reduction and implant loosening were not fully avoided by use of locking implants but incidence was low.
Keywords: acetabular fracture; string-of-pearls; VetLOX; locking compression plates; internal fixation